2016
DOI: 10.1007/s11356-016-7298-5
|View full text |Cite
|
Sign up to set email alerts
|

Styela plicata: a new promising bioindicator of heavy metal pollution for eastern Aegean Sea coastal waters

Abstract: As part of a research project, the concentrations of Cd, Cu, Pb, V, and Zn in the tissues of Styela plicata were investigated for the first time to determine if S. plicata is a suitable biological indicator for biomonitoring of heavy metals in eastern Aegean Sea coastal waters. To examine the relationships, heavy metal levels in suspended particulate matters (SPMs) and sediments were also determined. According to the results, the mean metal levels in SPM, sediments, and S. plicata samples could be arranged in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 79 publications
1
6
1
Order By: Relevance
“…Hence, Pb 2+ resulted to be about 2.5 times more bioconcentrated than Cd 2+ , giving an effective bioremediation level in seawater of 13% and 40% for Cd 2+ and Pb 2+ , respectively. The greater bioconcentration capacity observed for Pb 2+ in our study is consistent with data reported in literature concerning the analysis of the natural content of heavy metals in tissues of S. plicata (Aydın-Önen, S., 2016;Bellante et al, 2016;Philp et al, 2003). However, Cd 2+ and Pb 2+ content in S. plicata specimens involved in our bioremediation experiment are significantly greater than the content found in specimens collected from natural coastal areas.…”
Section: + and Pb 2+ Content In S Plicata Tissuesupporting
confidence: 91%
See 1 more Smart Citation
“…Hence, Pb 2+ resulted to be about 2.5 times more bioconcentrated than Cd 2+ , giving an effective bioremediation level in seawater of 13% and 40% for Cd 2+ and Pb 2+ , respectively. The greater bioconcentration capacity observed for Pb 2+ in our study is consistent with data reported in literature concerning the analysis of the natural content of heavy metals in tissues of S. plicata (Aydın-Önen, S., 2016;Bellante et al, 2016;Philp et al, 2003). However, Cd 2+ and Pb 2+ content in S. plicata specimens involved in our bioremediation experiment are significantly greater than the content found in specimens collected from natural coastal areas.…”
Section: + and Pb 2+ Content In S Plicata Tissuesupporting
confidence: 91%
“…The possibility of exploiting the combination of their abundant growth in polluted coastal areas and their ability to remove contaminants from seawaters has generated considerable interest. S. plicata is characterized by good properties as bioremediator and has been the subject of many studies for the bioconcentration of cadmium, lead, arsenic, mercury and heavy metal compounds in natural environments (Aydın-Önen, 2016;Bellante et al, 2016;Choi et al, 2014;Philp et al, 2003;Radford et al, 2000;), as well as bacteria (Stabili et al, 2016) and for the biodegradability of some organic chemicals (Cestone et al, 2008). It has been reported that they can bioconcentrate persistent compounds present in the aquatic environment, resulting quite resistant to their toxic effects (Petersen, 2007;Sumerel and Finelli, 2014;Abdul et al, 2015).…”
mentioning
confidence: 99%
“…Heavy metal ion stress in organisms is also a major focus of current research, and as tidal flat inhabitants, O. reevesii feeds on the surface soil of these flats and may very likely serve as an indicator of heavy metal ion pollution. This is a future research direction of our laboratory [41][42][43] . Although we compared data for O. reevesii of different sizes, because there is no consensus regarding the relationship between its growth stage and body weight, these experimental data need further confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this affinity, all trace metals are potentially toxic, binding to proteins or other molecules and preventing them from functioning in their intended role (Rainbow, 2002). Studies on the bioaccumulation of HMs in different marine organisms are thus essential in order to expand our knowledge regarding the relative metal bioavailability from different sources (Rainbow, 2002;Aydın-Önen, 2016). Determining the metal concentrations in organisms in the coastal region should constitute an essential part of any assessment and monitoring program of contaminants in the marine ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Ascidians are highly efficient filter-feeding organisms, able to accumulate and concentrate harmful toxicants when present even at low concentrations in their surroundings (Jiang et al, 2010;Treberg et al, 2012). Ascidians actively accumulate HMs, including manganese, iron, cadmium, magnesium, molybdenum, niobium, tantalum, chromium, titanium, and vanadium (Odate and Pawlik, 2007;Gallo and Tosti, 2015;Aydın-Önen, 2016). There have been a number of studies in recent years on ascidians as bio-indicators, using different measurements and indices (physiological, molecular, reproductive) the results of which demonstrate the potential of this group to function as a useful bio-indicator of contamination in the marine environment (Bellas et al, 2004;Radhalakshmi et al, 2014;Aydın-Önen, 2016;Bellante et al, 2016).…”
Section: Introductionmentioning
confidence: 99%